2022
DOI: 10.3390/ijerph19010501
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Hypothermia: 2021 Update

Abstract: Accidental hypothermia is an unintentional drop of core temperature below 35 °C. Annually, thousands die of primary hypothermia and an unknown number die of secondary hypothermia worldwide. Hypothermia can be expected in emergency patients in the prehospital phase. Injured and intoxicated patients cool quickly even in subtropical regions. Preventive measures are important to avoid hypothermia or cooling in ill or injured patients. Diagnosis and assessment of the risk of cardiac arrest are based on clinical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 155 publications
2
87
0
11
Order By: Relevance
“…Patients with signs of cardiovascular instability, cardiac arrest, or core temperatures <30 °C, are transported directly to a hospital with stand-by extracorporeal life support (ECLS) for active rewarming. Remaining patients are triaged to the nearest, appropriate hospital for passive and/or minimally invasive active rewarming (Lott et al, 2021;Paal et al, 2022). In accidental hypothermic patients, one pharmacological strategy to prevent or treat HCD is to elevate cardiac contractility (Dietrichs, Sager and Tveita, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with signs of cardiovascular instability, cardiac arrest, or core temperatures <30 °C, are transported directly to a hospital with stand-by extracorporeal life support (ECLS) for active rewarming. Remaining patients are triaged to the nearest, appropriate hospital for passive and/or minimally invasive active rewarming (Lott et al, 2021;Paal et al, 2022). In accidental hypothermic patients, one pharmacological strategy to prevent or treat HCD is to elevate cardiac contractility (Dietrichs, Sager and Tveita, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical or battery-powered heat packs that do not require an external source of electricity or hot water bottles should be stockpiled for active external rewarming. A review of the diagnosis and treatment of accidental hypothermia can be found in this special issue [79].…”
Section: Treatment Of Hypothermia After a Natural Disastermentioning
confidence: 99%
“…The development of effective strategies for the prevention of accidents/emergencies in mountain sports requires, beside updated knowledge derived from observational (epidemiological) studies, the inclusion of up-to-date findings from basic research. For example, information on cardiovascular and musculo-skeletal strain during hiking, climbing, skiing, cycling, etc., under different ambient conditions (e.g., altitude, cold, heat) is extremely helpful to advise healthy and in particular diseased individuals on the selection of and how to prepare for mountain sports activities [ 10 , 11 , 12 , 13 , 14 ]. Furthermore, knowledge on pathophysiological mechanisms triggering high-altitude illnesses (e.g., acute mountain sickness, high-altitude cerebral and pulmonary edema) is a prerequisite for the prevention and appropriate treatment of those illnesses as well [ 15 , 16 , 17 ].…”
Section: Examples For Research Ideasmentioning
confidence: 99%